Perkutane bildgeführte Radiofrequenzablation von Nierentumoren: Update 2015 - Sommer, Christof-Matthias; Stampfl, Ulrike; Kauczor, Hans-Ulrich (Der Urologe, 2015)
BackgroundStage I renal cell carcinoma is a malignancy with a relatively good prognosis. The incidence of all renal cell carcinomas is approximately 9/100,000 persons. There are nearly 15,000 newly diagnosed patients every year (men twice as often as women).TrendIn the last decade, a trend away from radical open resection towards nephron-sparing approaches has been observed. Currently, partial nephrectomy is the surgical gold standard for the treatment of small renal tumors. However, excellent clinical results are obtained using percutaneous radiofrequency ablation (RFA): low complication rates and preservation of the renal function.ResultsPrimary and secondary technical success rates are 69-100% and 90-100%, respectively. In large series, major complication rates of RFA of 0-14% are reported. A relevant deterioration of renal function after RFA is very rare. The 5-year local recurrence-free survival rates, metastasis-free survival rates, cancer-specific survival rates, and overall survival rates are 88-93, 95-100, 98-100, and 58.3-85%, respectively. In this context, the lack of appropriate long-term data is often cited as a limitation.ConclusionDifferent meta-analyses come to the conclusion that in case of adequate tumor and patient selection RFA shows oncologic results comparable with surgical resection. Accepted indications for RFA are T1 renal tumors in patients with advanced age, significant comorbidities, reduced renal function, single kidney, and/or no wish for operation. Predictors for the success include tumor size and location as well as operator experience. To define the real efficacy of RFA in the treatment of renal tumors, randomized controlled clinical long-term studies are indicated.